2002
DOI: 10.1177/030802260206500204
|View full text |Cite
|
Sign up to set email alerts
|

Some Factors influencing Occupational Engagement for People with Schizophrenia Living in the Community

Abstract: With the emergence of occupational science, there has been renewed interest in the health benefits of occupational engagement and a call for more research into the occupational nature of humans. Engaging in occupations is known to have a positive effect on an individual's health and sense of wellbeing. A common feature of people with schizophrenia, however, is a decrease in volition and a reduction in the occupations performed. This study explored some of the influences on occupational engagement for people wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 36 publications
4
35
0
1
Order By: Relevance
“…In particular, more depressive symptoms were associated with perceiving less valued occupations while more general psychopathology was related to worse satisfaction with daily occupation. The finding that more severe psychiatric symptoms were linked with less occupational value and satisfaction could indicate that the target group, along with perceiving worsening mental problems, decrease their engagement in social contacts and everyday occupations, as reported elsewhere (36).…”
Section: Discussionsupporting
confidence: 57%
“…In particular, more depressive symptoms were associated with perceiving less valued occupations while more general psychopathology was related to worse satisfaction with daily occupation. The finding that more severe psychiatric symptoms were linked with less occupational value and satisfaction could indicate that the target group, along with perceiving worsening mental problems, decrease their engagement in social contacts and everyday occupations, as reported elsewhere (36).…”
Section: Discussionsupporting
confidence: 57%
“…Emerson et al (1998) noted the common assumption that the symptom of anhedonia dampens the potential for enjoyment and pleasure from activities for people with psychosis. However, this was not supported by the data in many studies listed under this theme (Legault and Rebeiro 2001, Chugg and Craik 2002, Deegan 2002, Hitch 2009). …”
Section: My Emotions and Identitymentioning
confidence: 88%
“…Other researchers have found these factors to be important in making the activity meaningful and engaging to the performer. Chug and Craik (26) found that enjoyment and pleasure were important factors influencing occupational engagement. Hvalsoe and Josephsson (12) found that a strong indicator for meaningfulness is the presence of a close connection between occupation and the personal values and preferences of the individual.…”
Section: Discussionmentioning
confidence: 99%